2023
DOI: 10.3390/cancers15082378
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Alleviates Cancer Cachexia and Prevents Muscle Wasting via Activating SIRT1

Abstract: Skeletal muscle wasting is the most remarkable phenotypic feature of cancer cachexia that increases the risk of morbidity and mortality. However, there are currently no effective drugs against cancer cachexia. Ursolic acid (UA) is a lipophilic pentacyclic triterpene that has been reported to alleviate muscle atrophy and reduce muscle decomposition in some disease models. This study aimed to explore the role and mechanisms of UA treatment in cancer cachexia. We found that UA attenuated Lewis lung carcinoma (LLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In the current study, we sought to identify a new nutritional approach to maintaining healthy skeletal muscle in dogs. To this end, we developed a novel canine dietary supplement containing ursolic acid, a natural dietary compound that inhibits atrophy-associated mRNA expression and improves skeletal muscle health in non-canine species [9,[12][13][14][15][16][17][18][19]. Consistent with its effects in non-canine species, dietary supplementation with ursolic acid was safe and well tolerated by dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, we sought to identify a new nutritional approach to maintaining healthy skeletal muscle in dogs. To this end, we developed a novel canine dietary supplement containing ursolic acid, a natural dietary compound that inhibits atrophy-associated mRNA expression and improves skeletal muscle health in non-canine species [9,[12][13][14][15][16][17][18][19]. Consistent with its effects in non-canine species, dietary supplementation with ursolic acid was safe and well tolerated by dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that ursolic acid also reduces skeletal muscle atrophy in mouse models of chronic kidney disease [14], cancer [15], and spinal cord injury [16]; improves muscle function, health span, and lifespan in C. elegans and Drosophila [17,18]; and significantly increases strength in humans [19]. Mechanistically, ursolic acid acts directly on differentiated skeletal muscle cells from both humans and mice, where it alters muscle mRNA expression in a way that helps to maintain cellular processes that are critically important for the normal structure and function of skeletal muscle [8,9,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early detection of cancer patients with cachexia can potentially lead to interventions to counteract this process and improve quality of life and overall survival. Several blood biomarkers have been proposed to identify cancer cachexia; however, their clinical utility has been limited only to certain cancer types and they have not been universally adopted in the clinical setting [10][11][12]. The molecular mechanisms responsible for the development of cancer cachexia have not been fully defined [13,14].…”
Section: Pathophysiologymentioning
confidence: 99%
“…As the main components of rosemary, ursolic acid, carnosic acid, carnosol, rosmarinic acid, betulinic acid, and other components are considered effective components with anti‐tumor activity (Farhadi et al., 2023). Ursolic acid alleviates cancer cachexia through the activation of SIRT1 and the consequent down‐regulation of the phosphorylation of nuclear factor‐ κ B (NF‐κB) and STAT3 (Tao et al., 2023). Carnosic acid increases the expression of the proteins (HSPA5, ATF4, XBP1, and ER chaperones) involved in the unfolded protein response reflecting ER stress (Figure 7), and it participates in the inhibition of proliferation of human myeloid leukemia cells without inducing apoptosis (Cattaneo et al., 2015; Valdes et al., 2017).…”
Section: Biological Activities Of Rosemary Extractmentioning
confidence: 99%